A violência de gênero como experiência trágica na contemporaneidade: estudo de "Insubmissas lágrimas de mulheres", de Conceição Evaristo - Simone Teodoro Sobrinho (2015)
In this work I discuss gender violence in the collection of short stories Insubmissas lágrimas de mulheres, by Conceição Evaristo. The point of departure for this discussion is the assumption that the submission of women imposed by patriarchy at the beginning of civilization is tragic (according to the tragic conception of Raymond Williams) and has been perpetuated by power structures within the androcentric habitus, whose main strategy for maintaining the masculine status quo is to control the symbolic system. The work identifies, in Evaristo's text, tragic dramatizations in which female voices fight such oppression